CYCLOSPORINE-INDUCED GINGIVAL OVERGROWTH IN RENAL TRANSPLANT RECIPIENTS - Ana Maria Filioreanu; Andrada Raluca Doscas; Andrei Nicolau; Violeta Trandafir; Cristina Popa (Romanian Society of Oral Rehabilitation, 2018)
Gingival overgrowth is one of the most frequent side effect of immunosuppressive therapy with cyclosporine A in renal transplant patients. The exact pathogenesis of this pathology is uncertain but several influencing factors have been hypothesized such as age, gender, genetic predisposition, oral hygiene status, pharmacokinetic variables, immunological changes and concomitant use of other medications. Current treatment options for this pathology include conservative measures (plaque control, oral hygiene improvement, drug replacement) associated or not with surgical therapy. The oral specialist plays an integral role on the transplant team in establishing a clinical protocol that assists the organ transplant recipient in maintaining optimal oral health.